Catechol-hydrazone conjugates for the rapid functionalization of magnetite nanoparticles with cell targeting groups. Issue 1688 (9th May 2014) - Coxon, Thomas; Almond, Andrew; Gough, Julie E.; Webb, Simon J.
ABSTRACT: The condensation of hydrazides with aldehydes has been found to be a simple and rapid method for synthesizing catechol-terminated coating reagents for magnetite nanoparticles. This approach allowed the production of biotin- and polyethylene glycol-functionalized nanoparticles, whose interaction with 3T3 fibroblast cells has been assessed. The cellular location of these nanoparticles was imaged by fluorescence microscopy, which was made possible by co-coating with a porphyrin-catechol conjugate. Images show significant interactions between biotinylated nanoparticles and 3T3 fibroblasts, but those with a polyethylene glycol coating did not interact.